Achieving sustainable construction in the developing countries Of Southeast Asia - Shafii, Faridah; Arman Ali, Zainab; Othman, Mohamed Zahry (2006)
Sustainable construction is a way for the building industry to move towards achieving sustainable development, taking into account environmental, socioeconomic and cultural issues. Differing approaches and differing economic markets lead to different priorities. This paper presents the construction scenario of Southeast Asia and the developments in sustainable construction taking place in the region. Barriers to the implementation of sustainable construction are discussed. A list of recommendations was proposed to drive sustainable construction in the region. In conclusion, the status of sustainable construction in Southeast Asia is still in its infancy. The lack of awareness, training and education and ineffective procurement systems are among the major barriers for sustainable construction in the region. In some countries public policies and regulatory frameworks do not encourage the development of the construction sector. Besides the needs for capacities, technologies and tools, total and ardent commitment by all players in the construction sectors including the governments and the public at large are required in order to achieve sustainable construction in South-East Asia.